Disturbance-observer Based Prescribed-performance Control for PMSM in Electric Vehicles - NI Shuangfei; DAI Yuchen; CAI Qicheng; SUN Zhongyang (Kongzhi Yu Xinxi Jishu)
Aiming at the accurate speed tracking control of electric vehicles (EV) driven by permanent magnet synchronous motors (PMSM) under external load torque disturbances, this paper proposes an approach for prescribed performance back-stepping control based on a disturbance observer. Firstly, a controller was designed using the back-stepping technique, and a second-order sliding mode differentiator was introduced to approximate the derivative of the virtual control law, which can solve the "differential explosion" problem in traditional back-stepping control techniques. Secondly, in order to reduce the influence of motor load disturbances in the driving process of EV, a novel disturbance observer was proposed, bolstering the anti-interference capability of system. In addition, to achieve the preset high transient and steady-state speed tracking performance, a prescribed performance control strategy was incorporated to guarantee tracking errors within predefined boundaries. Finally, the Lyapunov function was utilized to verify the system stability. The simulation results showed that, compared with traditional PI control, the designed controller significantly increased motor speed tracking precision by more than 5 times, demonstrating a superior speed tracking performance and enhanced anti-interference capability.